The Effect of Inlet Air Velocity on the Reduction of Moisture Content in Drying Catfish With a Capacity of 2 Kg - Intang, Ambo; Junita, Boni; Ilmi, Bahrul; Rusnadi, Rusnadi; Wulandari, Enasty Pratiwi (FLYWHEEL : Jurnal Teknik Mesin Untirta, 2024)
One way to preserve or extend the shelf life of fishery products is by drying. However, the obstacle that exists in the community is that the preservation method is not maximized. Drying techniques using mechanical devices or artificial drying to overcome the shortcomings of conventional drying methods. In this study, drying catfish was carried out using coconut shell material as a smoking tool. The purpose of this study was to determine the effect of temperature on the drying rate in a dryer with a capacity of 2 kg of starch fish as an ingredient for smoking. The inlet air variations used in this study are 0.7 m/s, 0.8 m/s, 0.9 m/s, 1.0 m/s and 1.1 m/s. The results of this study indicate that the variation of inlet air 1.1 m/s is the variation that most reduces the water content in catfish as much as 15.08%. The reduction of moisture content of the material will increase if the inlet air flow velocity is increased. The drying process is influenced by temperature and airflow velocity. The results obtained by using a dryer that uses coconut shell charcoal are very efficient and economical because coconut shell charcoal is very easy to obtain and can be obtained at an affordable price.